2016
DOI: 10.1080/13691058.2016.1182217
|View full text |Cite
|
Sign up to set email alerts
|

Social and psychological correlates of unprotected anal intercourse among Hispanic-American women: implications for STI/HIV prevention

Abstract: Heterosexual anal intercourse is associated with increased risk for HIV and other sexually transmitted infections. Research on the social and psychological risk factors associated with heterosexual unprotected anal intercourse among Hispanic women in the USA is limited. We examined demographic, mental health, relationship power, sexual self-efficacy, self-esteem, acculturation and HIV knowledge as correlates of unprotected anal intercourse among 514 HIV-negative Hispanic women, 18 to 59 years of age, residing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…This mirrors the findings of Reynolds, Fisher and Rogala (2015) in which heterosexual women identified anal penetration as less risky if practiced with a trusted longterm partner. While described as sometimes being more intimate than vaginal sex and leading to greater orgasm, participants in Reynolds, Fisher and Rogala's study were more concerned about risk (see also McBride 2018;Villar-Loubet et al 2016). This is not to endorse notions of anal sex as inherently risky but to recognise that dominant cultural discourses still often position it as such.…”
Section: Discussionmentioning
confidence: 96%
“…This mirrors the findings of Reynolds, Fisher and Rogala (2015) in which heterosexual women identified anal penetration as less risky if practiced with a trusted longterm partner. While described as sometimes being more intimate than vaginal sex and leading to greater orgasm, participants in Reynolds, Fisher and Rogala's study were more concerned about risk (see also McBride 2018;Villar-Loubet et al 2016). This is not to endorse notions of anal sex as inherently risky but to recognise that dominant cultural discourses still often position it as such.…”
Section: Discussionmentioning
confidence: 96%
“…In addition to the well-known protective factors such as wearing condoms and being in a monogamous sexual relationship, studies have also shown that other factors such as social norms, acculturation, socioeconomic issues (food insecurity), and interpersonal issues (e.g., higher power of male sex partner) may play a role, namely they may increase risk of HIV infection among substance abusers (Ebrahim, Davis, & Tomaka, 2016; Gelpí-Acosta et al, 2016; Villar-Loubet et al, 2016). However, these protective factors were not addressed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Research related to HIV acquisition among women, particularly minority women living in Southern states, has primarily focused on gaining an understanding of the individual and sociocultural factors that influence the practice of risky sexual behaviours (Mallory 2008; Mullinax et al 2016; Nunn et al 2012; Paranjape et al 2006; Smith 2015; Teitelman et al 2015; Villar-Loubet et al 2016). Trust, the imbalance of power and an unequal gender ratio have been found to be important factors that influenced women’s use of condoms when engaging in risky sexual activity, especially in the case of long-term relationships.…”
Section: Introductionmentioning
confidence: 99%